A History of Modern Lebanon - Second Edition (Edition 2) - Traboulsi, Fawwaz (Pluto Press, 2012)
This is the second updated edition of the first comprehensive history of Lebanon in the modern period. Written by a leading Lebanese scholar, and based on previously inaccessible archives, it is a fascinating and beautifully-written account of one of the world's most fabled countries. Starting with the formation of Ottoman Lebanon in the 16th century, Traboulsi covers the growth of Beirut as a capital for trade and culture through the 19th century. The main part of the book concentrates on Lebanon's development in the 20th century and the conflicts that led up to the major wars in the 1970s and 1980s. This edition contains a new chapter and updates throughout the text. This is a rich history of Lebanon that brings to life its politics, its people and the crucial role that it has always played in world affairs.